Efektivitas Dan Keamanan Vaksin Covid-19 : Studi Refrensi - Nugroho, Setiyo Adi; Hidayat, Indra Nur (Jurnal Keperawatan Profesional, 2021)
Various strategies and development of the Covid-19 vaccine have been carried out for the control of the Covid-19 pandemic. Various vaccines have undergone clinical trials with promising results in various countries. The effectiveness and safety and short- and long-term side effects of vaccines are a major concern in clinical trials in these strategies and developments. Purpose: The purpose of this study is to find out the effectiveness and safety of the Covid-19 vaccine so that it can inform and increase public confidence in the Covid-19 vaccine through a reference study approach. Method: The research method we use here is a reference study using electronic databases through journals from international and national. Google Scholar, science direx, elsiver, Pubmed are used as the main Journal database for this reference study. Results: From the results of reference studies found that all vaccines in clinical trials have promising effectiveness and safety. The Pfizer-BiONTech vaccine is a vaccine that has a good level of effectiveness and safety with a value of 94.6% and does not cause serious side effects. Double-dose vaccination further improves the immune response in younger and older adults. Conclusion: The Covid-19 vaccine in clinical trials all demonstrates promising immunogenicity with varying levels of protective effectiveness and an acceptable safety profile.